Effects of Varying Storage Conditions on the Vigour of Fresh Seeds of Ekebergia capensis - Kibet, R. L.; Too, E. J.; Omari, A.; Meso, M. (Africa Environmental Review Journal, 2022)
Ekebergia capensis is a popular indigenous tree valued for its medicinal uses. However, it is an endangered tree species because of overexploitation and its slow regeneration rate in nature. Production of this tree is through seedlings from seeds with desirable vigour. There is limited knowledge on post-harvest storage of seeds of Ekebergia capensis without significant loss of seed vigor. This study was conducted in order to establish optimum storage conditions and period of storage of fresh seeds. This study investigated the effects of different moisture contents (MC) and storage temperature regimes on seed vigour loss of E. capensis seeds for a period 90 days. The fresh seeds were dried to three moisture contents (MC) (15%, 25% and 35%) and three storage temperature regimes (-5 o C, 10 o C and 25 o C) for a period of 30, 60 and 90 days. The stored seeds were retrieved at an interval of 30 days for vigour tests. Data analysis was carried using GLM statistical Model (GenSTAT.16) version. Findings from current study revealed that E. capensis seeds with higher moisture content of 35% stored across the tested temperature regimes viz: -5 o C, 10 o C and 25 o C maintained significantly higher vigour compared to other seeds with lower moisture content (25% and 15%) stored across all temperature regimes. Furthermore, seeds with 35% MC stored at 10 o C retained the highest vigour as storage period progressed to 90 days. A positive correlation existed between seed vigour and MC. Seed vigour decreased in the order of 35%>25%>15% MC. This study recommends that fresh seeds of E. capensis can be desiccated to a moisture content of 35 % and stored at 10 o C for 30 days without significant loss of vigor.